Geology and emplacement history of the Nuevo Rosario plutonic suite in the southern Peninsular Rangers batholith, Baja California, México - Peña Alonso, Tomás Alejandro; Delgado Argote, Luis Alberto; Weber, Bodo; Velasco Tapia, Fernando; Valencia, Víctor (Sociedad Geológica Mexicana, 2012)
The Cretaceous Nuevo Rosarito plutonic suite is located in the southern part of the Peninsular Ranges batholith (~28.7 °N). It is hosted by a suite of Jurassic granitoid rocks dated at 151.6 Ma (U-Pb single zircon ages) and by Late Jurassic - Early Cretaceous volcanic and volcaniclastic rocks. Host rocks display solid-state fabrics related to a deformational event that occurred before the emplacement of the Nuevo Rosarito plutonic suite. The composition of the suite ranges from gabbro to granite. The suite is sub-alkaline and it is divided into three mafic and four felsic units. The geochemical composition of the felsic units varies from metaluminous to peraluminous, and shows arc-related geochemical signatures. Structural and geochemical data suggest that the emplacement of the plutonic suite took place in two episodes. The first one is defined by the intrusion of mafic units in which dioritic bodies were emplaced within a gabbroic body along NNE-SSW oriented extensional fractures. The second episode is defined by the intrusion of three felsic units during a NE-side up, syn-emplacement movement that occurred around 108.4 Ma.